A Standardized Approach to Quantitative Analysis of Nicotine in e-Liquids Based on Peak Purity Criteria Using High-Performance Liquid Chromatography. (9th August 2018) - Gholap, Vinit V.; Kosmider, Leon; Halquist, Matthew S.
Abstract : The use of electronic cigarettes (e-cigarettes) is a growing trend in population. E-cigarettes are evolving at a rapid rate with variety of battery powered devices and combustible nicotine refills such as e-liquids. In contrast to conventional cigarettes which are studied well for their toxicity and health effects, long-term clinical data on e-cigarettes are not available yet. Therefore, safety of e-cigarettes is still a major concern. Although the Food and Drug Administration (FDA) has recently started regulating e-cigarette products, no limits on nicotine and other ingredients in such products have been proposed. Considering the regulatory requirements, it is critical that reliable and standardized analytical methods for analyzing nicotine and other ingredients in e-cigarette products such as e-liquids are available. Here, we are reporting a fully validated high-performance liquid chromatography (HPLC) method based on nicotine peak purity for accurately quantifying nicotine in various e-liquids. The method has been validated as per ICH Q2(R1) and USP <1225> guidelines. The method is specific, precise, accurate, and linear to analyze nicotine in e-liquids with 1 to >50 mg/mL of nicotine. Additionally, the method has been proven robust and flexible for parameters such as change in flow rate, column oven temperature, and organic phase composition, which proves applicability of the method over wide variety of e-liquids in market.